Underpricing PHENOMENON IN COMPANY FINANCIAL AND NON-FINANCIAL STOCK EXCHANGE IN INDONESIA (Case Study in BEI) - Cahyono, Andri; Legowo.,M.Si.,Akt, Drs. H.Herman (Accounting, 2009)
Underpricing is a condition in which the average market price of the new company´s stock went public, usually in a matter of days or weeks is higher than the bid price (Gumanti, 2002). The phenomenon of underpricing is a short-term phenomenon of several studies mentioned as a result of the underwriters that suppress the price to avoid risk. Because basically that determine stock prices in the primary market is corporate issuers deal with underwriters. Underpricing phenomenon can ditemuipada when companies do initial public offerings (IPO). The understanding of IPO (Initial Public Offering) is an event where for the first time a company sells or offers shares to the general public (Public) in the capital market. When the company for the first time its offering of its shares in the primary market, the offering price has not been established to represent the price of the issuer company. Underpricing not only can be viewed through a number of capital gains enjoyed by investors on the first day the shares traded on the stock, but also must be considered how the market return and consider the risk factors. So in this study used a measurement to explain the phenomenon of underpricing with the abnormal return, namely the difference between actual returns with the expected return. Keywords : underpricing, company financial, non financial